Penolakan Kebijakan Relokasi dan Implikasinya terhadap Hak Asasi Pedagang di Cisoka, Kabupaten Tangerang - Nur Amalia Zahra; Siti Mariyatul Koimah; Abi Robian (Innovations in Multidisciplinary Education Journal, 2024)
This study examines the rejection of the relocation policy stipulated in PERBUP Kabupaten Tangerang No. 60 of 2016 by traders in the Cisoka District. Findings indicate that the majority of traders oppose the policy due to the prohibition of street vendors (PKL) in the new market and the imposition of fees for public access. This situation significantly impacts the traders' income, potentially lowering their standard of living. The rejection reflects human rights issues, specifically the traders' right to work and earn a decent living. Dissatisfaction arises from a policy that lacks support and imposes access fees on the public. The study emphasizes the importance of involving traders in the formulation of policies affecting their livelihoods. The government is urged to review the relocation policy to be more inclusive and consider the aspirations and needs of the community. Overall, this research provides insights into the negative impacts of relocation policies that do not take into account the needs and rights of traders, highlighting the necessity of a fairer and more sustainable approach in policy-making to support the overall welfare of the community.